2021
DOI: 10.36923/jicc.v21i1.6
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Intercultural Communication in Malaysian Public Universities from the Perspective of Anxiety/Uncertainty Management (AUM) Theory

Abstract: The mission to promote national unity has become more strenuous with the decline of intercultural engagement among multicultural students in Malaysian public universities. Underpinned by Anxiety/Uncertainty Management (AUM) theory, this article examines barriers to intercultural communication by integrating ethnocentrism as an additional barrier. Based on a quantitative approach, 449 valid responses were collected from undergraduates from five public universities in Malaysia. Partial-least-squares software (Sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Dixson et al (2017) found that nonverbal immediacy behaviors, based upon students’ perceptions of an instructor’s time, tone, and effort, promote engagement in the online classroom. Generally, there is an inverse relationship between student engagement and anxiety (Mazer, 2017; Rajan et al, 2021). Thus, reducing anxiety and apprehension increases engagement, which leads to positive student outcomes (Singh, 2020).…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Dixson et al (2017) found that nonverbal immediacy behaviors, based upon students’ perceptions of an instructor’s time, tone, and effort, promote engagement in the online classroom. Generally, there is an inverse relationship between student engagement and anxiety (Mazer, 2017; Rajan et al, 2021). Thus, reducing anxiety and apprehension increases engagement, which leads to positive student outcomes (Singh, 2020).…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…The government also provides assistance to poor students to continue their education, especially in the face of high dropout rates (Suprastowo, 2021). Another policy is the effort to provide textbooks through an e-book system so that students can upload, own, and stimulate students to think creatively (Sari, 2019;Rajan, Alam, Kia, & Subramaniam, 2021). Recently, the government has also made efforts to provide information and communication technology as a responsive and adaptive attitude to be developed and utilized in learning (Lazear, 2002;Pearlman, 2006;NIE'S, 2015;Agung, 2017;Ministry of Education and Culture, 2021).…”
Section: Governance Policymentioning
confidence: 99%